Assessment of the Photobiomodulation Effect of a Blue Diode Laser on the Proliferation and Migration of Cultured Human Gingival Fibroblast Cells: A Preliminary In Vitro Study - Etemadi, Ardavan; Taghavi Namin, Soheil; Hodjat, Mahshid; Kosarieh, Emad; Hakimiha, Neda (Journal of Lasers in Medical Sciences, 2020)
Introduction: Photobiomodulation therapy (PBM) is emerging as an effective strategy for the management of wound healing. The application of red and near infra-red light sources in laser therapy has been the subject of most researches in recent literature. Considering the lack of sufficient evidence in assessing the blue light in PBM, we aimed to investigate the photobiomodulation effect of a blue diode laser on the proliferation and migration of cultured human gingival fibroblast cells as a preliminary in vitro study. Methods: Human gingival fibroblast cells were irradiated with a blue diode laser at a 445 nm wavelength. Irradiation was done using three different powers of 200 mW (irradiation times of 5, 10,15, and 20 seconds); 300 mW (irradiation times of 5, 10, and 15 seconds); and 400 mW (irradiation times of 5 and 10 seconds). The fibroblast cells without laser exposure were considered as control. After 24 hours of incubation, the MTT assay and the wound scratch test were performed on the cells to investigate the biomodulation effect of the blue laser on the proliferation and migration of the cells respectively. The results were analyzed by one-way ANOVA and a post-hoc Tukey test with a P value <0.05 as a statistical significance level. Results: PBM with blue diode laser at power densities of 400 mW/cm2 with irradiation times of 10 and 15 seconds corresponding to energy densities of 4 and 6 J/cm2 exerted the statistically significant positive effect on both proliferation and migration of gingival fibroblast cells. Conclusion: Considering the encouraging findings of this study, PBM with blue diode laser can promote proliferation and migration of human gingival fibroblasts, the key cells involved in the process of oral wound healing.